Our last best chance the pursuit of peace in a time of peril - Abdullah II, King of Jordan, 1962- (Viking, 2011)
The eldest son of Jordan's King Hussein, the author had not expected to ascend to the throne; his father's brother had long been crown prince. But he was chosen by the king on his deathbed. Both a memoir and a frank discussion of how to solve problems in the Middle East.